Pengaruh Lama Pengomposan Terhadap Sifat Kimia Kompos Tandan Kosong Kelapa Sawit Dengan Inokulum Trichoderma, Azobacter, dan Limbah Cair Pabrik Kelapa Sawit - Ahmad Mustangin; Yulius Beni; Yuni Selvianti Sari; Danie Indra Yama (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
Oil Palm Empty Fruit Bunches (OPEFB) have only been used as organic fertilizer by placing it between plants without prior treatment, as a result, the decomposition process of OPEFB takes a long time and produces toxic ammonia. The composting process with variations in composting time and decomposer is a solution in utilizing OPEFB as compost with the best quality. The purpose of this study was to analyze the effect of composting time with Trichoderma sp, Azotobacter, and Palm Oil Mill Effluent (POME) inoculums on the quality of OPEFB compost. The study was structured using a 2-factor Randomized Block Design, which was repeated 3 times. The first factor was the variation of decomposers (Trichoderma sp, Azotobacter, POME) and the second factor is the composting time of 20 days, 40 days and 60 days. The observed parameters including temperature, pH, levels of N, P, K, C, and C/N. The data were statistically analyzed using Analysis of Variance (ANOVA) then further tested with the Least Significant Differences (LSD) test with 95% confidence level if significant effect occured. The treatment gave a significant effect on the levels of N, P and K in OPEFB compost. OPEFB compost had a temperature of 27.33 – 29.33°C, the highest N content was 0.7162%, P content was 0.2222% - 0.8423%, K content was 0.3953% - 0.9043% and C 20.19% - 25.66% which is in accordance with SNI 19-7030-2004 regarding compost quality. The value of the C/N ratio of OPEFB compost products produced from the all treatment was 29.86 – 98.66 so that it did not meet the compost maturity standard of 10 – 20. The production of OPEFB compost can be done with a longer composting time than the treatment in the study, in order to increase maturity value.Keywords: Compost; Composting time; Decomposers; OPEFB